2014
DOI: 10.1371/journal.pone.0111170
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissection of the Clostridium botulinum Type B Hemagglutinin Complex: Identification of the Carbohydrate and E-Cadherin Binding Sites

Abstract: Botulinum neurotoxin (BoNT) inhibits neurotransmitter release in motor nerve endings, causing botulism, a condition often resulting from ingestion of the toxin or toxin-producing bacteria. BoNTs are always produced as large protein complexes by associating with a non-toxic protein, non-toxic non-hemagglutinin (NTNH), and some toxin complexes contain another non-toxic protein, hemagglutinin (HA), in addition to NTNH. These accessory proteins are known to increase the oral toxicity of the toxin dramatically. NTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Consistent with this finding, HA/A binds the monomeric EC1–EC2 domains with an affinity that is much stronger than the affinity of E-cadherin homo-dimerization [40••,44,47]. The model that disruption of the adherens junctions of epithelial cells by the HA complex opens up a paracellular route to facilitate BoNT absorption has been supported by extensive in vitro and ex vivo studies [33•,40••,42] (Figure 3), and was further confirmed by an in vivo study showing that an E-cadherin binding deficient L-PTC/A has markedly decreased oral toxicity in mouse [40••]. …”
Section: Structure and Function Of The Ha Complexmentioning
confidence: 78%
See 2 more Smart Citations
“…Consistent with this finding, HA/A binds the monomeric EC1–EC2 domains with an affinity that is much stronger than the affinity of E-cadherin homo-dimerization [40••,44,47]. The model that disruption of the adherens junctions of epithelial cells by the HA complex opens up a paracellular route to facilitate BoNT absorption has been supported by extensive in vitro and ex vivo studies [33•,40••,42] (Figure 3), and was further confirmed by an in vivo study showing that an E-cadherin binding deficient L-PTC/A has markedly decreased oral toxicity in mouse [40••]. …”
Section: Structure and Function Of The Ha Complexmentioning
confidence: 78%
“…HA70 binds one Neu5Ac-containing carbohydrate [16••]. HA33, on the other hand, binds one galactose-containing carbohydrate through its C-terminal β-trefoil domain in serotypes A and B [16••,33•]. HA33 serotype C, however, displays a lower affinity for galactose, but carries an extra Neu5Ac-binding site near the Gal-binding pocket [30,34].…”
Section: Structure and Function Of The Ha Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal epithelial cell line Caco-2 has been widely used to characterize the transport of BoNTs in vitro (Couesnon et al, 2008; Lee et al, 2013; Matsumura et al, 2008; Sugawara et al, 2014). In a trans-well assay, Caco-2 cells are differentiated on a permeable poly-carbonate support to form a polarized columnar cell monolayer resembling the small intestinal epithelial layer with high transepithelial resistance against passive diffusion of ion and solutes.…”
Section: Resultsmentioning
confidence: 99%
“…HA70 and HA33 carry an N-acetylneuraminic acid (Neu5Ac) and a galactose (Gal) binding site, respectively. Therefore, each HA complex comprises a total of nine glycan-binding sites, which allow multivalent interactions with host carbohydrates to enrich the toxin complex on the intestinal surface (Lee et al, 2013; Matsumura et al, 2015; Sugawara et al, 2014; Yao et al, 2014). The HA complex then interacts with E-cadherin, a major host adhesion protein, to disrupt the E-cadherin mediated cell-cell adhesion and open the paracellular route facilitating the transepithelial delivery of BoNT (Lee et al, 2014b; Matsumura et al, 2008; Sugawara et al, 2010).…”
Section: Introductionmentioning
confidence: 99%